2011
DOI: 10.1093/molehr/gar027
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of recurrent hydatidiform moles in China: correlations between NLRP7 mutations, molar genotypes and reproductive outcomes

Abstract: Hydatidiform mole (HM) is a human pregnancy with abnormal embryonic development. NLRP7 is a major autosomal recessive gene responsible for recurrent molar pregnancies and associated reproductive wastage in patients from several populations. Here, we report NLRP7 mutation analysis in 35 unrelated Chinese patients with recurrent reproductive wastage, including at least one HM. We describe three new protein-truncating mutations in NLRP7 and show the presence of three founder mutations in China and Asian populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 28 publications
4
40
0
Order By: Relevance
“…All these data reflect the notion that the impact of genetic defects due to a single mutated NLRP7 allele may be modulated by environmental and other genetic factors and consequently, they are not always associated with reproductive wastage for all patients and do not impede all of their pregnancies. 33 Our findings add further insight to the hypothesis that NLRP7 heterozygosity may be involved in the development of sporadic molar pregnancies, either complete or partial moles, associated or not with other forms of reproductive failure. We also suggest a comparison of the status of DNA methylation on imprinted genes between cases of sporadic HM with heterozygous NLRP7 mutations and other cases with no mutation.…”
Section: Commentsupporting
confidence: 69%
See 2 more Smart Citations
“…All these data reflect the notion that the impact of genetic defects due to a single mutated NLRP7 allele may be modulated by environmental and other genetic factors and consequently, they are not always associated with reproductive wastage for all patients and do not impede all of their pregnancies. 33 Our findings add further insight to the hypothesis that NLRP7 heterozygosity may be involved in the development of sporadic molar pregnancies, either complete or partial moles, associated or not with other forms of reproductive failure. We also suggest a comparison of the status of DNA methylation on imprinted genes between cases of sporadic HM with heterozygous NLRP7 mutations and other cases with no mutation.…”
Section: Commentsupporting
confidence: 69%
“…Previous reported cases were from patients of various ethnic origins who were either homozygous or compound heterozygous for NLRP7 mutations; however, cases of patients with 1 NLRP7 defective allele have been rarely reported (Table). 26,28,33,34 We found that 3 mutation carriers had CHM and 2 had PHM. Exhaustive histologic criteria were used by 2 experienced pathologists to classify these cases.…”
Section: Commentmentioning
confidence: 69%
See 1 more Smart Citation
“…NLRP7 is mutated in 88% and 60% of analyzed familial and singleton cases of RHMs, respectively. [9][10][11][12][13][14] Recently, we demonstrated that ex vivo lipopolysaccharides (LPS)-stimulated peripheral blood mononuclear cells (PBMCs) from patients with mutations and rare variants in NLRP7 have defective interleukin-1 beta (IL-1b) and tumor necrosis factor secretion but normal to higher intracellular levels of pro-and mature-IL-1b. 13,15 The requirement of NLRP7 for normal IL-1b secretion by macrophages was also confirmed in in vitro studies after NLRP7 silencing using small interfering RNA (siRNA).…”
Section: Introductionmentioning
confidence: 99%
“…Both genes were repeatedly seen to be responsible for recurrent hydatidiform moles (RHMs) [54][55][56][57][58][59][60][61]. Despite being diploid biparental, therefore with a normal biparental contribution to their genomes, RHM tissues lack maternal methylation marks on several maternally imprinted genes.…”
Section: Scmc Involvement In Epigenetic Reprogramming Of Zygotesmentioning
confidence: 99%